ADAM17‐mediated CD44 cleavage promotes orasphere formation or stemness and tumorigenesis in HNSCC. (16th October 2013) - Kamarajan, Pachiyappan; Shin, Jae M; Qian, Xu; Matte, Bibiana; Zhu, Joey Yizhou; Kapila, Yvonne L.
Abstract CD44, an extracellular matrix (ECM) receptor, has been described as a cancer stem cell marker in multiple cancers, including head and neck squamous cell carcinoma (HNSCC). HNSCC orasphere formation or stemness was characterized by cleavage of CD44, and thus we hypothesized that this proteolytic processing may be critical to stemness and tumorigenesis. We tested this hypothesis by examining the mechanisms that regulate this process in vitro and in vivo, and by exploring its clinical relevance in human specimens. Sphere assays have been used to evaluate stemness in vitro. Spheres comprised of HNSCC cells or oraspheres and an oral cancer mouse model were used to examine the significance of CD44 cleavage using stable suppression and inhibition approaches. These mechanisms were also examined in HNSCC specimens. Oraspheres exhibited increased levels of CD44 cleavage compared to their adherent counterparts. Given that disintegrin and metalloproteinase domain‐containing protein 17 (ADAM17) is a major matrix metalloproteinase known to cleave CD44, we chemically inhibited and stably suppressed ADAM17 expression in HNSCC cells and found that these treatments blocked CD44 cleavage and abrogated orasphere formation. Furthermore, stable suppression of ADAM17 in HNSCC cells also diminished tumorigenesis in an oral cancer mouse model. Consistently, stable suppression of CD44 in HNSCC cells abrogated orasphere formation and inhibited tumorigenesis in vivo. The clinical relevance of these findings was confirmed in matched primary and metastatic human HNSCC specimens, which exhibited increased levels of ADAM17 expression and concomitant CD44 cleavage compared to controls. CD44 cleavage by ADAM17 is critical to orasphere formation or stemness and HNSCC tumorigenesis.